2009
DOI: 10.1007/s00439-009-0641-x
|View full text |Cite
|
Sign up to set email alerts
|

SCA8 repeat expansion: large CTA/CTG repeat alleles in neurological disorders and functional implications

Abstract: Spinocerebellar ataxia type 8 (SCA8) involves bidirectional expression of CUG (ATXN8OS) and CAG (ATXN8) expansion transcripts. The pathogenesis of SCA8 is complex and the spectrum of clinical presentations is broad. In the present study, we assessed the SCA8 repeat size ranges in Taiwanese Parkinson's disease, Alzheimer's disease and atypical parkinsonism and investigated the genetic variation modulating ATXN8 expression. Thirteen large SCA8 alleles and a novel ATXN8 -62 G/A promoter SNP were found. There is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Severe ataxia with inability to walk independently is usually not a typical feature for HD or SCA8 at this disease stage. Wu et al detected SCA8 expanded alleles in PD and atypical Parkinsonism suggesting that SCA8 CTG repeat expansion may play a role in the development of sporadic PD or atypical Parkinsonism [2]. The fact that Parkinsonian symptoms of our patient remained unresponsive to dopaminergic medication supports the hypothesis of possible involvement of SCA8 in the pathogenesis of atypical Parkinsonism.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Severe ataxia with inability to walk independently is usually not a typical feature for HD or SCA8 at this disease stage. Wu et al detected SCA8 expanded alleles in PD and atypical Parkinsonism suggesting that SCA8 CTG repeat expansion may play a role in the development of sporadic PD or atypical Parkinsonism [2]. The fact that Parkinsonian symptoms of our patient remained unresponsive to dopaminergic medication supports the hypothesis of possible involvement of SCA8 in the pathogenesis of atypical Parkinsonism.…”
Section: Discussionsupporting
confidence: 53%
“…As there is an overlapping gene ATXN8, the polyglutamine expansion protein possibly contributes through toxic effects, too [10]. The clinical presentation of large repeat expansions is variable; the phenotype spectrum ranges from healthy subjects, patients with cerebellar ataxia to patients with typical and atypical Parkinson disease [2]. In addition coexistence with SCA1, SCA6, 16q-ADCA, FRDA have been reported.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Wu et al detected an abnormal expansion of SCA8 in four patients with typical PD (1.5%) from among 264 patients with PD [ 19 ]. The range of the SCA8 repeat size was analyzed in a Taiwanese PD cohort, and large SCA8 alleles (66–120 repeats) and a novel ATXN8 −62 G/A promoter SNP were found [ 78 ]. The same group also performed a structural analysis in a cohort of 569 PD cases and 547 ethnically matched controls, and they found that individuals carrying the AA genotype exhibited a decreased risk of developing PD than those with the GG + GA phenotypes [ 71 ].…”
Section: Sca8mentioning
confidence: 99%